Hybrid solar still with addition of charcoal and oil palm fiber ash for seawater desalination - Jamil, Roslan (2019)
Solar still is an evaporator where solar energy is used to produce fresh water from saline or brackish water but suffer low thermal efficiency and low yield. Therefore, a solar still with biomass application as alternative solar thermal energy storage is attractive to explore because it is a simple technique for desalination, cheap, low energy consumption and environmentally friendly. The objective of this research is to study the effect of solar still cover inclination angle, water depth and biomass (charcoal and oil palm fiber ash (OPFA)) application in solar still for seawater desalination. The solar still was designed and fabricated. The biomass, charcoal and OPFA, was used as thermal storage. The effect of depth of seawater (1cm to 4 cm,) the cover inclination angle (10 to 40) and biomass to seawater mass ratio (1:50, 1:100 and 1:500) were investigated. The experiment was carried out under sunny daylight for seven hours from 10.00 a.m. to 5.00 p.m. The water quality of spend seawater and evaporated water was analyzed by determining the pH, conductivity, total dissolve solid (TDS), Chemical Oxygen Demand (COD) and turbidity. The fresh and spent biomass were characterized by using Brunauer Emmet Teller (BET), X-Ray Detector (XRD) and Scanning Electromagnetic Microscope (SEM). The OPFA has high carbon and metal oxides content including SiO2, K2O, CaO and other traceable oxides. Meanwhile, the charcoal has high content of carbon and large pore sizes. The surface of charcoal and OPFA was stable after testified in the seawater. Without biomass application, it is found that 30º cover inclination angle contributed to the highest yield of evaporated water production (6.68 wt%). The depth of seawater at 1cm has the highest temperature (51 °C) and yielded 6.14 wt% of evaporated water. The present of charcoal and OPFA in solar still significantly enhanced the performance of solar still. It is found that highest yield of evaporated water was achieved when the biomass to seawater mass ratio was at 1:100. Addition of charcoal produces more fresh water than OPFA. A 17% of evaporated water yield and seawater temperature of 60 °C were achieved when charcoal was used in hybrid solar still. Meanwhile, 11.6 wt % of evaporated water yield and 53 °C of seawater temperature was achieved when OPFA was used. A 60 % and 58.5% reduction of COD was also obtained when charcoal and OPFA was used respectively. The pH, conductivity, COD and turbidity of the evaporated water that produced from solar still complied with drinking water quality standard. In conclusion, charcoal and OPFA application are able to increase the water temperature, produce more evaporated water and reduce the impurities in polluted water.